2013
DOI: 10.4103/0974-2727.115910
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Urogenital Cleaning with Paper Soap on Bacterial Contamination Rate While Collecting Midstream Urine Specimens

Abstract: Context:Urinary tract infection (UTI) is one of the major health problems. Urine culture is considered as a gold standard method for the diagnosis of UTI. But, improper sample collection can lead to contamination with normal urogenital flora. Use of any portable disinfectant that can reduce contamination rate would be the significant help in urine culture interpretation.Aims:To observe the effect of urogenital cleaning with paper soap on bacterial contamination rate while collecting specimens.Materials and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Studies based in secondary care have found varying accuracy of voided urine samples depending on their patient group, design and gold standard [ 14 – 18 ]. However, studies investigating symptomatic, otherwise healthy women seem to essentially reproduce our findings [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 79%
“…Studies based in secondary care have found varying accuracy of voided urine samples depending on their patient group, design and gold standard [ 14 – 18 ]. However, studies investigating symptomatic, otherwise healthy women seem to essentially reproduce our findings [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 79%
“…There may never be a suitable method to eliminate skin organisms that contaminate the specimen obtained via CCU. Previous studies have shown that cleaning of the perineum reduced contamination rates from 24 to 8%, but did not eliminate the incidence of contamination altogether …”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that cleaning of the perineum reduced contamination rates from 24 to 8%, but did not eliminate the incidence of contamination altogether. 20,22,23 Contamination rates in CCU samples trended towards being associated with gender, with female contamination rates being 16.4% and male contamination rates being 10.5%. The urinary stream in women is shorter and thus more likely to come into contact with skin prior to collection, increasing the possibility of contamination.…”
Section: Discussionmentioning
confidence: 99%
“…The nurse could alternatively straight catheterize the patient. Patients with bacteria in their urinalysis will need a separate specimen for culture and repeat catheterizations increase urethral irritation allowing bacteria to proliferate (Shrestha, Gyawali, Gurung, Amatya, and Bhattacharya, 2013).…”
Section: Geriatric Considerationsmentioning
confidence: 99%